Assessment of airborne polycyclic aromatic hydrocarbons in a megacity of South China: Spatiotemporal variability, indoor-outdoor interplay and potential human health risk. (July 2018) - Hu, Yuan-Jie; Bao, Lian-Jun; Huang, Chun-Li; Li, Shao-Meng; Liu, Peter; Zeng, Eddy Y.
Abstract: Although a number of studies have assessed the occurrence of atmospheric polycyclic aromatic hydrocarbons (PAHs) in indoor environment, few studies have systemically examined the indoor-outdoor interplay of size-dependent particulate PAHs and potential health risk based on daily lifestyles. In the present study, size-dependent particle and gaseous samples were collected both indoors and outdoors within selected schools, offices and residences located in three districts of Guangzhou, China with different urbanization levels during the dry and wet weather seasons. Results from measurements of PAHs showed that higher total PAH concentrations occurred in residential areas than in other settings and in indoor than in outdoor environments. Compositional profiles and size distribution patterns of particle-bound PAHs were similar indoors and outdoors, predominated by 4-and 5-ring PAHs and the 0.56–1.0 μm particle fraction. Statistical analyses indicated that outdoor sources may have contributed to 38–99% and 62–100% of the variations for indoor particle-bound and gaseous PAH concentrations, respectively. Incremental life cancer risk ( ILCR ) from human exposure to indoor and outdoor PAHs based on different lifestyles followed the order of adults > children > adolescents > seniors. All average ILCR values for four age groups were below the lower limit of the Safe Acceptable Range (10 −6 ). In addition, the ILCR value for adults (average: 7.2 × 10 −7 ; 95% CI: 5.4 × 10 −8 ‒2.5 × 10 −6 ), estimated from outdoor air PAH levels with 24-h exposure time, was significantly higher than our assessment results (average: 5.9 × 10 −7 ; 95% CI: 6.3 × 10 −8 ‒1.9 × 10 −6 ), suggesting the significance of assessing human inhalation exposure risks of indoor and outdoor PAHs in urban air based on daily lifestyles. Graphical abstract: Image 1 Highlights: Indoor airborne PAHs were contributed by indoor source and outdoor infiltration. Size distributions of particle-bound PAHs indoors and outdoors are similar. The inhalation exposure health risk to indoor and outdoor air PAHs was low for residents in Guangzhou. Abstract : Systematic investigation and assessment of PAHs are conducted to gain insight into the occurrence and estimate human respiratory exposure risk of indoor and outdoor air PAHs in an urban zone.